Implementation of Long Term Athlete Development (LTAD) to Sport Coach at KONI Pariaman City - Bahtra, Ridho; Aldo Naza Putra (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Increasing national sporting achievements will run well if it starts from the lower levels, namely districts and cities. From Kota Pariaman's participation in Porprov, Kota Pariaman has never once reached the best position (rank 1) in terms of medals, and has never even entered the top 10. Based on the results of interviews and observations in the field, there were findings that coaches' understanding of athlete coaching patterns was still low, especially in long-term coaching. The coach's lack of knowledge about athlete development can ultimately lead to the coach's inability to create training programs for long-term coaching. The approach method used in solving partner problems is 1) Workshop in order to increase the knowledge and understanding of trainers in long-term coaching patterns by providing material on Long Term Athlete Development and 2) Follow-up discussions in the context of monitoring and evaluation. The result of this activity is an increase in trainers' knowledge and understanding in creating long-term coaching programs.